The Role of Behavioral Approach In Financial Reporting Enhancement - سلمان عامر محمد; سلمان وفاء حسين (Journal of Economics and Administrative Sciences, 2016)
This study seeks to highlights on the behavioral approach in organization theory as modern and effective entrance in constructing this theory and reflection extent on the behavior of both the product and the information user (accountant and financial information). The study also focus on behavioral approach role in consolidating accounting concepts through making harmony between them so that the accountant can influence the user behavior with the concepts and principles of accounting in an effort to provide quality characteristic of accounting information produced by him in consistent with his behavior and information user and its impact on the decision making process by the latter. The study ended with a set of conclusions, the most important is that the behavioral approach became necessary to search the values in order to in flouence the decision maker based on accounting information, and the accountants behavior has a role in controlling the provision of qualitative characteristics of accounting information, which is reflected on the decision-maker.